2003
DOI: 10.1046/j.1365-4362.2003.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated mucocutaneous leishmaniasis resulting from chronic use of corticosteroid

Abstract: Mucocutaneous leishmaniasis is a granulomatous disease clinically characterized by ulcerated skin and mucosal lesions whose clinical manifestations can regress spontaneously, but with possible long subclinical evolution. The course of the disease is often related to the host immune response. The purpose of this article is to describe the clinical and microscopic findings of cutaneous and mucosal lesions of mucocutaneous leishmaniasis in a patient who presented an unusual form of the disease associated with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 10 publications
1
20
0
4
Order By: Relevance
“…For the human, however, it has been suggested that quiescent or slow-growing parasites could be reactivated and metastasize to mucocutaneous sites following immuno-suppressive treatment (Motta et al, 2003) or during in stress situations (Travi et al, 1988, 1996) which are perhaps not encountered in the laboratory model.…”
Section: Experimental Animal Models Of MCLmentioning
confidence: 99%
“…For the human, however, it has been suggested that quiescent or slow-growing parasites could be reactivated and metastasize to mucocutaneous sites following immuno-suppressive treatment (Motta et al, 2003) or during in stress situations (Travi et al, 1988, 1996) which are perhaps not encountered in the laboratory model.…”
Section: Experimental Animal Models Of MCLmentioning
confidence: 99%
“…As a result of immunosuppression of human immunodeficiency virus-positive patients, kidney and heart recipients, and chronic users of corticosteroids, a serious risk of reactivation of CL in MCL form is present. [19][20][21][22][23] On account of such complications, treatments should be started promptly after its diagnosis, so as to prevent mucosal metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only few case reports describing that systemic corticosteroid treatment may worsen mucocutaneous leishmaniasis or lead to a recurrence of the disease. 10,11 This is the first description of ML caused by L. major in a traveler as opposed to patients residing in endemic areas. The place of exposure in this patient was most likely North Africa, where he had traveled to Tunisia, Morocco, and Egypt 2 years before the occurrence of the disease.…”
Section: Discussionmentioning
confidence: 93%